Konsekuensi Penetapan Tarif Minimal Pelayanan Jasa Notaris sebagai Upaya Melindungi Hak Notaris Guna Kepastian dan Keadilan - Ramadhan, Muhammad Fajar (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Notaries have an important task in providing legal services to the public, particularly regarding the making of authentic deeds. The determination of minimum service rates for notaries by the Indonesian Notary Association (INI) is regulated in the Notary Code of Ethics with the aim of preventing unfair competition and protecting the rights of notaries. This research aims to analyze the form of the agreement on the determination of minimum service rates for notaries, evaluate the role of INI in determining these rates, and examine the legal consequences of violations of the minimum rate determination. This is a qualitative research with a single case study approach in Hulu Sungai Selatan Regency, South Kalimantan. Data was collected through in-depth interviews with notaries, clients, and other related parties, observations at notary offices, and studies of relevant documents. The determination of minimum rates by INI is carried out through a mechanism of study and evaluation by the INI Regional Administrators which is submitted to the INI Central Administrators to be determined nationally. This determination is a form of agreement that binds all INI members. Violations can be subject to sanctions from the INI organization as well as administrative sanctions from the Notary Supervisory Board. Obstacles in implementing the minimum rates include differences in operational costs between regions, resistance from notaries, weak monitoring and law enforcement, and a lack of flexibility in facing changing economic conditions. Efforts that can be made include determining varying rates, socialization and education, forming a supervisory body, a mechanism for rate adjustments, and maintaining a balance with consumer protection.